Nonhydrolyzable d‑phenylalanine-benzoxazole derivatives retain antitubercular activity. (15th January 2023) - Pepi, Michael J.; Chacko, Shibin; Kopetz, Nicole; Boshoff, Helena I.M.; Cuny, Gregory D.; Hedstrom, Lizbeth
Graphical abstract: Abstract: The emergence of drug resistant Mycobacterium tuberculosis, the causative agent of tuberculosis, demands the development of new drugs and new drug targets. We have recently reported that the d -phenylalanine benzoxazole Q112 has potent antibacterial activity against this pathogen with a distinct mechanism of action from other antimycobacterial agents. Q112 and previously reported derivatives were unstable in plasma and no free compound could be observed. Here we expand the structure-activity relationship for antimycobacterial activity and find nonhydrolyzable derivatives with decreased plasma binding. We also show that there is no correlation between antibacterial activity and inhibition of PanG, a putative target for these compounds.